A Framework for Testability Analysis from a Systems Architecture Perspective. Issue 3 (14th November 2018) - Efatmaneshnik, Mahmoud; Ryan, Michael J; Shoval, Shraga
ABSTRACT: In this paper, we study the effects of system architecture on testability. We present a probabilistic model of testability that enables us to study the relationships between system architecture and testability. A Markov Chain model obtains the quality of system after test as a function of its quality before test and the test quality. We focus on the costs and benefits associated with the modularization for testability. We show that choosing the proper testing architecture through careful modularization can enhance efficiency and effectiveness of system testing. We base the model on repetitive testing which means we will repeat the test after a fail test outcome.